KONSEP, PRAKTIK, DAN KONTEKSTUALISASI MANUSIA POLITIK DAN RUANG PUBLIK HANNAH ARENDT - Brenda Yanti, I Gusti Agung Ayu; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT   In analyzing Hannah Arendt's thoughts about political man, there are main concepts that first have to be understood, i.e. vita activa or fundamental human activities. From the concept, two characters can be concluded: first, political man is man who uses their thoughts actively, and the second character from political man is freedom. Political man is a free human. To get the identity, political human needs sphere called the public realm. Arendt defines public realm to be two definitions: the first definition is as public appearance, a place where the individual shows themselves in front of other people and the second definition is common world which means the whole condition resulting from man's creation that needs to be lived together. Keyword: Political Man, Vita Activa, Public Realm, Hannah Arendt.